Level of Students' Mathematical Literacy Based on Cognitive Conceptual Tempo (Reflective-Impulsive) - Sari, Pamiati Oktavia; Wulan, Eka Resti (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2024)
This research aims to describe students' mathematical literacy abilities based on their cognitive conceptual tempo. The research method used in this study is a qualitative descriptive approach. The research was conducted at SMKN 1 Ngasem in class XI-2 Design, Modeling, and Building Information. Data collection techniques in this research involved the use of tests and interviews. The tests were divided into two parts: the Matching Familiar Figures Test (MFFT) to gather data on students' cognitive styles (conceptual tempo) and a mathematical literacy test to assess the level of mathematical literacy abilities of the students. The results of this research indicate that reflective subjects were able to achieve a mathematical literacy level of 3 for S1 and level 4 for S2. Reflective students fall within the medium scale. Meanwhile, impulsive subjects achieved mathematical literacy indicators at level 1 and level 4 for S3, and level 1, level 3, and level 4 for S4. Impulsive students also fall within the medium scale. Furthermore, future researchers can explore more extensive mathematical literacy content and contexts.